An overview of the problems related to research in construction engineering, management and economics in Poland - Kapliński, Oleg; Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 2002)
Problems related to research on the organization, management, economics and technology in the construction industry in Poland are discussed and evaluated in this paper. Scientific and, more specifically, academic circles are characterised and alarming phenomena that accompany practicing the issues of organization and management in construction engineering are discussed: an increase of the number of employees with economic education, phenomena related to finance, staff feminization and fluctuations among other things. Trends observed in research works and changes in the subject matter of interest to participants at scientific conferences are pointed out. Publication activity, dissertations and international cooperation are discussed. Non-serial publications of the last three years are listed. The analysis is based on a questionnaire circulated by the Construction Management Section of the Civil Engineering Committee of the Polish Academy of Science, the members of which are the authors of this article. The questionnaire covered a period of ten years. Furthermore, proceedings from conferences organized domestically under the patronage of the said Section as well as the effect of a trilateral international cooperation between Lithuania, Germany and Poland have been used. Frist Published Online: 30 Jul 2012